2013
DOI: 10.1253/circj.cj-12-1355
|View full text |Cite
|
Sign up to set email alerts
|

Post-Stress Perfusion Abnormalities Detected on Myocardial Perfusion Single-Photon Emission Computed Tomography Predict Long-Term Mortality After Elective Abdominal Aortic Aneurysm Repair

Abstract: Background: After abdominal aortic aneurysm (AAA) repair, relatively low survival during long-term follow-up remains an unresolved issue. Stress myocardial perfusion single-photon emission computed tomography (SPECT) well predicts future mortality overall, as well as providing diagnoses of coronary artery disease. The prognostic value of myocardial SPECT findings after AAA repair, however, remains unclear. Methods and Results:This study followed 285 patients, all undergoing preoperative pharmacologic stress my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Our previous study concluded that evaluating preoperative pharmacologic stress by myocardial perfusion single-photon emission CT is a useful method for predicting long-term cardiovascular mortality in patients undergoing elective AAA repair. 33 This preoperative management strategy may be why CAD and severe COPD were not predictors of midterm survival in our cohort.…”
Section: Discussionmentioning
confidence: 76%
“…Our previous study concluded that evaluating preoperative pharmacologic stress by myocardial perfusion single-photon emission CT is a useful method for predicting long-term cardiovascular mortality in patients undergoing elective AAA repair. 33 This preoperative management strategy may be why CAD and severe COPD were not predictors of midterm survival in our cohort.…”
Section: Discussionmentioning
confidence: 76%